Analysis of Cargo Handling Efficiency on Mt. Golden Sky Hana: Procedures and Performance - Arief Supriatna; Boy Laksmana; Putri Dwi Jayanti (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research evaluates the cargo handling processes aboard the MT. Golden Sky Hana, focusing on the effectiveness of loading and unloading operations. Using qualitative methods, including direct observations and structured interviews, the study assesses procedural adherence, crew competency, equipment utilization, communication efficiency, and safety practices. The findings reveal that 95% of the cargo handling activities are rated as "Very Good," indicating high operational efficiency. The results underscore the effectiveness of current procedures, the strong knowledge and skills of the crew, and the effective use of equipment. Communication among crew members and adherence to safety protocols also contribute significantly to the success of the operations. The research highlights the importance of maintaining high standards in cargo handling practices and offers insights for further improvement. Continuous training, regular updates to procedures, and investment in equipment are recommended to enhance operational performance further.